Analisis Perbedaan Prinsip Produk Penghimpunan Dana (Funding) Perbankan Syariah dan Perbankan Konvensional - Khoiriyah, Ni'matul; Nikmah, Jumiatun; Istiqomah, Nur Hidayatul (Program Studi Perbankan Syariah, Fakultas Ekonomi dan Bisnis Islam, Institut Agama Islam Nahdlatul Ulama Tuban, 2023)
Abstract: The bank is an official state institution in the financial sector that has the task of withdrawing and disbursing public money. Banks are one type of trusted institution among the surrounding community. Banks that have a non-trivial task make the bank also registered in the law for its security. There are many banks in Indonesia, one of which is BSI. BSI is the only bank that applies sharia principles based on the Koran and hadith. The existence of these principles makes Islamic banks not carelessly choose transactions or cooperation with other parties or customers. Uniquely, Islamic banks also use a profit sharing system as their ratio. Whereas conventional banks use the deposit interest system as their ratio. That is why researchers are interested in conducting research on the difference between the principles of Islamic banks and conventional banks in fundraising products (funding). There are three types of fundraising products in both Islamic and conventional banks, namely checking accounts, savings accounts and time deposit accounts. The difference is that Islamic banks use wadi'ah contracts and mudharabah contracts. This study aims to introduce to all people that Islamic banks have their own uniqueness and characteristics. Therefore, it is necessary to explain the contracts involved in Islamic banking. In this study, researchers used qualitative techniques. There are two data sources: Primary and secondary data sources . The researchers conducted direct interviews with informants based on primary data. Abstrak: Bank merupakan Lembaga resmi negara di bidang keuangan yang mempunyai tugas menarik dan mengeluarkan uang masyarakat. Bank menjadi salah satu jenis Lembaga terpercaya dikalangan masyarakat sekitar. Bank yang memiliki tugas tidak sepele membuat bank juga tercatatat dalam undang-undang demi keamanannya. Ada banyak bank di Indonesia, salah satunya BSI. BSI satu-satunya bank yang menerapkan prinsip syariah berdasarkan Al-quran dan hadits. Adanya prinsip tersebut membuat bank syariah tidak sembarangan memilih transaksi atau kerja sama dengan pihak lain atau nasabah. Sistem yang menarik dalam bank syariah adalah penggunaan prinsip bagi hasil sebagai perbandingannya. Sedangkan bank konvensional menggunakan sistem bunga simpanan sebagai nisbahnya. Itu mengapa peneliti tertarik untuk melakukan penelitian tentang bedanya prinsip bank syariah dan bank konvensional pada produk penghimpunan dana (funding). Terdapat tiga jenis produk penghimpunan dana baik di bank syariah maupun bank konvensional, yaitu rekening giro, rekening tabungan dan rekening deposito. Penelitian ini bertujuan untuk mengenalkan pada seluruh masyarakat bahwa bank syariah memiliki keunikan dan ciri khas tersendiri. Dengan demikian diperlukannya penjelasan mengenai akad-akad yang tertuang dalam bank syariah. Sumber datanya promer dan sekunder. Para peneliti melakukan wawancara langsung dengan informan berdasarkan data primer.